Seeking justice, experiencing the state: criminal justice and real legal uncertainty in the Democratic Republic of Congo. Issue 3 (2nd September 2018) - Jacobs, Carolien
Abstract: This article studies criminal justice in the conflict-affected east of the DR Congo, showing that in cases involving serious injury or violent death, people expect the involvement of the state's justice system despite their doubts about its functioning. The paper uses an ethnographic approach to study how the state, in a context of fragility becomes visible to people in the particular domain of criminal justice. The data show that Congolese justice seekers hardly expect "real legal certainty, " but instead look for outcomes that come closest to their emic ideas about what is just and what is right. To access state justice, it is widely held necessary to have either money or connections with more powerful people. For those without such connections, resort to non-state justice, including popular justice, can be a viable alternative. The empirical data illustrate how a relational approach to the state can help in understanding people's experiences with and perceptions about the state and their reasons for resorting to state or non-state criminal justice provision. It thereby sheds light on how expectations about access to state justice and a lack of real legal certainty shape the existence of legal pluralism.